Evaluation of effectiveness of concentrated growth factor on osseointegration - Pirpir, Cagasan (Int J Implant Dent, 2017)
BACKGROUND: Growth factor-containing products have been reported to increase implant stability and accelerate osseointegration. Concentrated growth factor (CGF) can be used for this purpose with the growth factors it contains. The aim of this study is to assess the effect of CGF on implant stability and osseointegration. METHODS: Twelve patients with maxillary anterior toothless were included in the study. Implant cavities prepared in the study group were covered with CGF membrane before implant placement, but conventional implant placement was performed in the control group. Resonance frequency measurements were performed with the Osstell device intra-operatively, post-operatively, at the 1st week, and at the 4th week. RESULTS: The mean ISQ values were found to be 79.40 ± 2.604 for the study group and 73.50 ± 5.226 for the control group at 1st week, 78.60 ± 3.136 for the study group and 73.45 ± 5.680 for the control group at 4th week. The differences between the groups were statistically significant (p < 0.05). CONCLUSIONS: It was observed that the concentrated growth factor had positive effects on implant stabilization. The ISQ measurements at week 1 and week 4 were notably higher in the study group. Application of this material seems to accelerate osseointegration.